Observed Cost and Variations in Short Term Cost‐Effectiveness of Therapy for Ischemic Stroke in Interventional Management of Stroke (IMS) III. Issue 5 (May 2017) - Simpson, Kit N.; Simpson, Annie N.; Mauldin, Patrick D.; Palesch, Yuko Y.; Yeatts, Sharon D.; Kleindorfer, Dawn; Tomsick, Thomas A.; Foster, Lydia D.; Demchuk, Andrew M.; Khatri, Pooja; Hill, Michael D.; Jauch, Edward C.; et al.
Abstract : Background: Examination of linked data on patient outcomes and cost of care may help identify areas where stroke care can be improved. We report on the association between variations in stroke severity, patient outcomes, cost, and treatment patterns observed over the acute hospital stay and through the 12‐month follow‐up for subjects receiving endovascular therapy compared to intravenous tissue plasminogen activator alone in the IMS (Interventional Management of Stroke) III Trial. Methods and Results: Prospective data collected for a prespecified economic analysis of the trial were used. Data included hospital billing records for the initial stroke admission and subsequent detailed resource use after the acute hospitalization collected at 3, 6, 9, and 12 months. Cost of follow‐up care varied 6‐fold for patients in the lowest (0–1) and highest (20+) National Institutes of Health Stroke Scale category at 5 days, and by modified Rankin Scale at 3 months. The kind of resources used postdischarge also varied between treatment groups. Incremental short‐term cost‐effectiveness ratios varied greatly when treatments were compared for patient subgroups. Patient subgroups predefined by stroke severity had incremental cost‐effectiveness ratios of $97 303/quality‐adjusted life year (severe stroke) and $3 187 805/quality‐adjusted life year (moderately severe stroke). Conclusions: Detailed economic and resource utilization data from IMS III provide powerful evidence for the large effect that patient outcome has on the economic value of medical and endovascular reperfusion therapies. These data can be used to inform process improvements for stroke care and to estimate the cost‐effectiveness of endovascular therapy in the US health system for stroke intervention trials. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Registration number: NCT00359424.